Particulate concentration distribution in centrifugal air classifiers. (September 2018) - Barimani, Mohammad; Green, Sheldon; Rogak, Steven
Highlights: Using computational fluid dynamics we model particle motion in a centrifugal air classifier. Highly enhanced particulate concentrations near the rotor outer radius are predicted. This concentration enhancement occurs for a wide range of classifier operating conditions. The enhanced concentration might explain why a large number of very fine particles are rejected. Abstract: Centrifugal air classifiers are used to separate particles as small as 3 microns from a mixed-size dust. In this paper, the flow in a high-speed classifier is simulated. The 3-d air-phase Reynolds-averaged Navier–Stokes equations are solved in the classifier with two different turbulence closure models. The Discrete Phase Model, which neglects inter-particle interactions, is utilized to track particles in the airflow. The model also permits one to calculate particulate concentration contours in the classifier. We find that particles of diameter near the classifier cut-point are dramatically concentrated (by factors in excess of 100) in locations near the outer blade radius. We speculate that this high concentration makes particle–particle interactions much more important than expected based on the feed concentration, which could in turn reduce the acceptance of the smallest particles.